Recording of Falls in Elderly Fallers in Northern Greece and Evaluation of Aging Health-Related Factors and Environmental Safety Associated with Falls: A Cross-Sectional Study - Dimitrios Lytras; Evaggelos Sykaras; Paris Iakovidis; Konstantinos Kasimis; Ioannis Myrogiannis; Anastasios Kottaras (Occupational Therapy International)
Background. Elderly falls constitute a global problem with huge social and economic aspects. Fall risk factors are both intrinsic (physical and psychological) and extrinsic (related with environmental safety). Aim. To record both intrinsic and extrinsic risk factors and their correlation in elderly fallers in order to suggest specific guidelines for their medical care and environmental modification inside and outside the home. Method. The study involved 150 elderly fallers (median age 70 (67-74)), who completed a record containing information on known risk factors related to their health status, as well as information on the conditions and causes that led to the fall. Each fall was considered an independent event, while measurements were performed regarding balance, strength, their functional ability, and the fear of a possible fall. Descriptive analysis and frequency analysis were used to record the health and activity status of the participants as well as the fall-related environmental factors. Severity of each fall event across a variety of locations was examined using the Kruskal-Wallis one-way analysis of variance. Multiple linear regression was applied to examine the effect of the mean values of functional tests and medical records on the number of fall events. Results. In the span of 12 months, a total of 304 fall events were recorded. Regarding location, 77.6% occurred indoors; more frequent were the bedroom (28.6%) and the bathroom (28%). The interior stairs (10.5%), the kitchen (4.9%), and the living room (3.3%) were the less frequent locations. Concerning danger, falling on the interior stairs caused the longest hospitalization, followed by the kitchen and the bathroom. Extrinsic factors that led to both indoor and outdoor falls were the administration of psychotropic medication, poor space ergonomics, lack of basic safety standards, and poor lighting conditions. Vision problems and dizziness resulted in more falls than other intrinsic factors. Furthermore, reduced performance in the FICSIT-4 test and the 30-Second Chair Stand Test, as well as high scores in the CONFbal–GREEK questionnaire and the Short FES-I, shows a linear relationship with an increased number of falls. Conclusions. Ergonomic interventions can help prevent indoor elderly falls. Poor construction and lack of adequate lighting mainly cause outdoor falls. Regular eye examinations, management of vertigo, improvement of the balance and strength of the lower limbs, and reduction of fear of impending falls are the intrinsic factors that help prevent falls the most.